Study on International Genetically Modified Food Labeling System via the Perspective of Consumers’ Right to know - Deng, Yifan (Transactions on Economics, Business and Management Research, 2024)
China has been promoting the industrialization of genetically modified technology and has implemented stringent labeling regulations to safeguard consumers’ access to information. The labeling system plays a crucial role in linking technology commercialization with market consumption. Yet, in practical applications, the labeling regulations has deepened consumer prejudice and impeded the progress of the genetically modified food business. The genetically modified food labeling systems of the United States, the European Union, and Japan merely cover most of the labeling types worldwide. Either adhering to scientific reliability principle and adopting a voluntary labeling system, or adhering to risk prevention principle and adopting a mandatory labeling system, or implementing the principle of combining rigidity and flexibility and adopting a compromise management, different countries have established genetically modified food labeling systems based on their own circumstances. Learning from global advanced practices and tailoring them to the characteristics of China，we have the potential to boost our own genetically modified labeling system progressing.